2003
DOI: 10.1097/00004872-200310000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Increased C-reactive protein concentrations in never-treated hypertension

Abstract: Systolic blood pressure and pulse pressure, but not diastolic blood pressure, are predictors of plasma C-reactive protein concentrations in patients with newly diagnosed, never-treated hypertension, irrespective of the potential proinflammatory action of traditional cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 31 publications
11
70
0
2
Order By: Relevance
“…20 The other one may be related to inflammatory stimulation on vascular endothelium. Similar to the earlier investigations, 31,32 this study showed that the patients with hypertension had increased CRP, which is a marker for the presence of inflammation. Recently, we found that that CRP is able to induce EMP production in human umbilical vein endothelial cells (HUVECs).…”
Section: Discussionsupporting
confidence: 90%
“…20 The other one may be related to inflammatory stimulation on vascular endothelium. Similar to the earlier investigations, 31,32 this study showed that the patients with hypertension had increased CRP, which is a marker for the presence of inflammation. Recently, we found that that CRP is able to induce EMP production in human umbilical vein endothelial cells (HUVECs).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in agreement with previous studies showing that higher levels of CRP are related to hypertension and pulse pressure [26,[30][31][32][33][34][35]. However, after lifecourse adjustments for confounders, the associations with pulse pressure and hypertension were markedly attenuated and no longer significant, suggesting that these associations are not causal.…”
Section: Discussionsupporting
confidence: 92%
“…The median hsCRP concentration that we found in the subjects without atherosclerosis, is close to that reported for never-treated hypertensive individuals (1.8 mg/l) by Schillaci et al 19 On the other hand, it is also similar to the average concentration in over 5000 apparently healthy Americans (1.6 mg/l). 17 Taken together, our findings suggest that elevated hsCRP concentrations should be attributed to atherosclerosis and not to hypertension by itself.…”
Section: Discussionsupporting
confidence: 89%
“…17,18 hsCRP is not only a predictor of overt cardiovascular disease, but it also has been associated with the presence and severity of subclinical systemic atherosclerosis as well as the presence of hypertension. 19,20 Previous angiographic studies have only visualized a limited part of the vascular tree, that is, carotid and coronary arteries. However, in patients suspected of having renovascular disease, both renal arteries and the abdominal aorta are visualized, thus allowing a relatively large part of the arterial system to be evaluated for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%